تفسیر قرآن میں اقوالِ تابعین کا اختلاف ، انواع اور وجوہات: Differences in the Statements of the Tabi’in in the Interpretation of the Quran: Types and Causes - ur Rehman, Shafiq; Hussain, Dr. Mubashir (Al-Amīr Research Journal for Islamic Studies, 2024)
Exegesis of the Holy Qur’an is a vital scientific field in which scholars have explained the verses of the Qur’an at different times. Tabi’een are those individuals who received knowledge directly from the Companions and carried forward the interpretations of the Qur’an and Sunnah. The period of the Tabi’een is of special importance in that they helped to better understand the meanings of the Qur’an ’Ijtihad’ in the light of the traditions of the Companions and their interpretation. However, differences of interpretation arose between them which became an important part of Islamic intellectual heritage. In order to understand the reasons for the disagreements among Tafseers, we need to examine their scholarly background, principles, and methods. The first reason is the difference in their education and training. Some followers acquired knowledge of the Qur’an directly from the Companions, while others received education from various scholars and madrasahs. Tafsirs of subjects of different educational backgrounds became a major cause of differences. Another reason is geographical conditions. The Tabieen lived in different areas, such as Makkah, Madinah, Kufa, and Basra. Each region had its own special traditions and cultures, which influenced the exegetical thinking of the followers. For example, the followers of Makkah mostly relied on the tafsir of Abdullah bin Abbas, while those in Kufa relied on the tafsir of Abdullah bin Masud. The third reason is the difference in oral traditions. The Tabieen received the interpretation of the Qur’an in the form of tradition from the Companions, due to which some traditions differed. This difference was based on different interpretations of oral traditions which later caused differences among the Tabi’een. The fourth reason is the importance of Ijtihad. The Tabi’een used their own ijtihadat to interpret the Qur’an and included their own thinking and principles. Their ijtihad sometimes differed, leading to differences in interpretation happened. Keywords: Exegesis, Tabi’een, Interpretation, Differences, Ijtihad.